Answer:
(9,9)
Step-by-step explanation:
Answer:
24m - 28
Step-by-step explanation:
Given the expression (6m−7)⋅4, we are to simplify it. Using the distributive law;
A(B+C) = AB + AC [A is distributed over B and C]
For the expression (6m−7)⋅4, we will distribute 4 over 6m and -7 as shown;
(6m−7)⋅4 = 4(6m) - 4(7)
(6m−7)⋅4 = 24m - 28
Hence (6m−7)⋅4 = 24m - 28
Answer:
b ≤ 26/3
Step-by-step explanation:
All we have to do is divide both sides by 3
3x/3 ≤ 26/x
x ≤ 8.67
Answer:
30
Step-by-step explanation:
the base is 10 the height is 3
10 x 3 = 30
Answer:
Coefficient
Step-by-step explanation:
These numbers are the ones in front of the variables in the beginning of an equation also known as coefficients. The numbers all by themselves without variables are constants. The first term is usually the number with the biggest exponent.